The course and factors associated with recovery of whiplash-associated disorders: an updated systematic review by the Ontario protocol for traffic injury management (OPTIMa) collaboration. (3rd September 2021) - Shearer, Heather M.; Carroll, Linda J.; Côté, Pierre; Randhawa, Kristi; Southerst, Danielle; Varatharajan, Sharanya; Wong, Jessica J.; Yu, Hainan; Sutton, Deborah; van der Velde, Gabrielle; Nordin, Margareta; Gross, Douglas P.; et al.
Abstract: Purpose: To update the findings of the Bone and Joint Decade 2000–2010 Task Force on Neck Pain and Its Associated Disorders (Neck Pain Task Force) on prognostic factors for whiplash-associated disorder (WAD) outcomes. Materials and methods: We conducted a systematic review and best-evidence synthesis. We systematically searched MEDLINE, EMBASE, CINAHL and PsycINFO from 2000–2017. Random pairs of reviewers critically appraised eligible studies using the Scottish Intercollegiate Guidelines Network criteria. Results: We retrieved 10, 081 articles. Of those, 100 met inclusion criteria. After critical appraisal, 74 were judged to have low risk of bias. This adds to the 47 admissible studies found by the Neck Pain Task Force. Twenty-two related to course of recovery; 59 to prognostic factors in recovery; and 16 reported other WADs outcomes. Some studies related to more than one category. Findings suggest that half of those with WADs will experience substantial improvement within three months and cessation of symptoms within six months. Among factors associated with recovery are post-crash psychological factors, including expectations for recovery and coping. Conclusions: Our review adds to the Neck Pain Task Force by clarifying the role of prognostic factors. Evidence supports the important role of post-crash psychological factors in WADs recovery. Systematic Review Registration Number: CRD42013004610